Tinjauan Yuridis Tindakan Preventif oleh PPATK (Pusat Pelaporan Dan Analisis Transaksi Keuangan) di Indonesia dan di Amerika Serikat - Wishnu Kurniawan; Rosna Rosna (Journal of Judicial Review, 2017)
Since money play a vital role in every person’s living, they are willing to try anything to gain as much money as they can even by doing crimes and they will surely try to hide their crime footsteps in order to avoid from being found out, so they will do an act called money laundering. There is an unit that plays an important role in every country which is called INTRAC (Indonesian Financial Transaction Reports and Analysis Centre) in Indonesia and is called FinCEN (Financial Crimes Enforcement Network) in United States of America. The purpose of this study is to describe clearly and carefully about the similarities and differences of INTRAC (Indonesian Financial Transaction Reports and Analysis Centre) in Indonesia and FinCEN (Financial Crimes Enforcement Network) in United States of America reviewed from preventive action, to know about their obstacles, and the strengths and weaknesses of both institutions in doing the preventive action, then to decide which FIU (Financial Intelligence Unit) is better in fighting against money laundering. This research uses normative research and then comparative method. Secondary data is collected using the library research. As all datas are collected, those datas are then being processed and analyzed qualitatively which means to group data and compile systematically. Further conclusions drawn related to this study, then decribed descriptively. Based on the results of this study showed that by reviewing from the main tasks and functions and competency related to the preventive action, INTRAC in Indonesia and FinCEN in United States of America have most significant similarity in being FIU that they have the same main task in fighting against the money laundering. Besides that, they also have differences and have very own obstacles, strengths, and weaknesses. According to the comparation between INTRAC and FinCEN, we can then know that FinCEN which was built in 1990 turns out to the better than INTRAC which was then built in 2002 in preventing and combating money laundering because FinCEN’s role is better in fighting against money laundering.